TINJAUAN ATAS PENGAKUAN PENDAPATAN METODE PERSENTASE PENYELESAIAN PADA PT WASKITA BETON PRECAST TBK - Ngaisah Fitania, (2020)
Companies engaged in construction that completed their construction contracts one year ago were more than one years old, so the company must learn how to calculate and regulate the method of payment of the company, the company used the calculation method when receiving its valuation. PT Waskita Beton Precast Tbk uses applicable accounting standards. Revenue is approved only if the company has economic benefits that flow to the company substantially. The company will accept the contract within the contract that has been committed. Because the recognition of revenue is related to contract costs, applied standards must comply with applicable standards. In revenue recognition on construction contracts, PT Waskita Beton Precast Tbk uses the percentage of completion and the revenue is approved only when the Official Reports of Payment (BAP) is issued. The approved amount is the percentage of completion multiplied by the contract value. Then the revenue will be disclosed and presented.